(untitled) (Research, Society and Development, 2020)
This study proposed to characterize the effects of feeding based on whole corn grain diet on the dynamics of clinical parameters and biochemical metabolites of confined cattle. Twenty adult mixed-breed cattle, with an average weight of 300 kg, were used, divided into two experimental groups. The experimental group (G1; n=15), composed of animals fed only Max Beef Grain Whole diet and the control group (G2; n=5), composed of animals, fed with sugarcane bagasse and the Max Beef Grain Whole grain diet, in the 30:70 ratio. All animals were submitted to clinical observations, blood collection by jugular venipuncture and ruminal fluid. The animals that received Max Beef Grain Whole Diet were clinically demonstrated with incomplete ruminal movements, mild ruminal tympania and diarrhea with whole corn grains. He did not show changes in hematology or in the concentration of fibrinogen. They presented a lower ruminal pH value during the whole experimental period, with impaired rumen fluid population, reduction of the methylene blue reduction test and absence of sedimentation and absent flotation. It was concluded that the inclusion of diets containing Max Beef Whole Grain for confined cattle causes chronic ruminal acidosis and compromises the physical-chemical and microbiological characteristics of the ruminal fluid.